CD62L expression marks SARS-CoV-2 memory B cell subset with preference for neutralizing epitopes - Onodera, Taishi; Sax, Nicolas; Sato, Takashi; Adachi, Yu; Kotaki, Ryutaro; Inoue, Takeshi; Shinnakasu, Ryo; Nakagawa, Takayuki; Fukushi, Shuetsu; Terooatea, Tommy; Yoshikawa, Mai; Tonouchi, Keisuke; et al. (Science advances, 2023)
Severe acute respiratory syndrome coronavirus 2–neutralizing antibodies primarily target the spike receptor binding domain (RBD). However, B cell antigen receptors (BCRs) on RBD-binding memory B (B mem ) cells have variation in the neutralizing activities. Here, by combining single B mem cell profiling with antibody functional assessment, we dissected the phenotype of B mem cell harboring the potently neutralizing antibodies in coronavirus disease 2019 (COVID-19)–convalescent individuals. The neutralizing subset was marked by an elevated CD62L expression and characterized by distinct epitope preference and usage of convergent V H (variable region of immunoglobulin heavy chain) genes, accounting for the neutralizing activities. Concordantly, the correlation was observed between neutralizing antibody titers in blood and CD62L + subset, despite the equivalent RBD binding of CD62L + and CD62L − subset. Furthermore, the kinetics of CD62L + subset differed between the patients who recovered from different COVID-19 severities. Our B mem cell profiling reveals the unique phenotype of B mem cell subset that harbors potently neutralizing BCRs, advancing our understanding of humoral protection. Phenotypic profiling of SARS-CoV-2 memory B-cells reveals neutralizing subset.